Knowledge about first aid, wound management and vaccination for the cases of dog bite: a cross-sectional study among the students of a management and technology institute in western Uttar Pradesh - Singh, Anuj; Agarwal, Medhavi; Singh, Arun; Katyal, Rashmi; Joshi, H. S.; Khan, Swati (International Journal Of Community Medicine And Public Health, 2017)
Background: About half the world’s population is living in countries/territories where dog rabies still exists and is potentially exposed to rabies. In 2005 there were 12,700 symptomatically identifiable furious rabies deaths in India; taken as a whole 1.1 deaths per lac population; mostly in males (62%), in rural areas (91%), and in children below the age of 15 years (50%). The aims and objectives of the study were to ascertain the knowledge about the first aid and vaccination measures and to assess the awareness about management, dressing and suturing of wound following dog bite among students of a management college in the Western Uttar Pradesh. Methods: A cross sectional study was conducted in a professional institute of Bareilly district selected by simple random sampling between August 2016- January2017, data was collected with the help of a questionnaire related to the assessment of knowledge regarding wound management. Results: 96% believe in proper wound management of animal bite, 37% think dressing of wound is necessary, 40% think immediate suturing of wound is important, where as 90% study subjects were aware of Anti-rabies vaccine. Conclusions: Awareness assessment about the wound management is almost satisfactory. Since, majority of subjects know the right measure of first-aid and believe in proper wound management after dog bite along with the knowledge about anti-rabies vaccine.